2005
DOI: 10.1021/jp044777g
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into Sulfobetaine-Stabilized Cu Nanoparticle Formation:  Toward Development of a Microfluidic Synthesis

Abstract: The mechanistic aspects of the formation of sulfobetaine-stabilized copper nanoparticles were investigated by using in situ XANES (X-ray absorption near edge structure), UV-vis spectroscopy, and reaction calorimetry. The tetracoordinated sulfobetaine-Cu(II) complex was reduced to a stable sulfobetaine-Cu(I) complex prior to the formation of sulfobetaine-stabilized copper nanoparticles. The stability of the Cu(I) complex was found to be sensitive to the concentration of the sulfobetaine stabilizer and the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 45 publications
(79 reference statements)
0
80
0
3
Order By: Relevance
“…[35]). Shim et al [36] incorporated copper complexes into cellulose acetate and observed formation of copper and Cu 2 O nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…[35]). Shim et al [36] incorporated copper complexes into cellulose acetate and observed formation of copper and Cu 2 O nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…neither significant chemical shift of the absorption edge to higher energy nor a systematically higher white line intensity, or a lower pre-edge intensity is observed [31]. Similar to the standard hcp Co foil, the clear pre-edge feature (the first inflection point at 7712.4 eV) and the presence of a shape resonance at about 7759.7 eV indicate that one is dealing with the metallic Co phase [31,35,38]. Little magnetic bias observed in their hysteresis loops further confirms that these Co NPs and Co@Au NPs are free of oxidative impurities or the oxidative layers are too thin to be detected [36,47].…”
Section: Resultsmentioning
confidence: 92%
“…Cobalt nanoparticles were prepared by the reduction of CoCl 2 (99.9%, anhydrous) in tetrahydrofuran (THF, 99.90% pure packaged under nitrogen) using lithium hydrotriethylborate (LiBH(C 2 H 5 ) 3 , 1 M solution in THF) as a reducing agent and 3-(N,Ndimethyldodecylammonia)-propanesulfonate (SB12, 98%) as a stabilizer in the microfluidic reaction process, which has been discussed extensively in our previous publications [25,28,31,32,35,[37][38][39][40][41]. Co@Au nanoparticles with different shell thickness were prepared by the combination of the displacement method and the reduction-deposition process using KAuCl 4 as Au source, which was described in our recent publication.…”
Section: Preparation Of Co Nps and Co@au Core Shell Npsmentioning
confidence: 99%
“…It is demonstrated that single-source precursors favour the formation of mono-disperse metal nanoparticles Small copper nanoparticles with a narrow size distribution were produced in a microfluidic device by Kumar et al [26], and Packirisamy et al [27]. The most important property of microdevice-prepared copper nanoparticles is an improved stability to oxidation, very important for any application.…”
Section: Synthesis Of Inorganic Nanoparticlesmentioning
confidence: 99%